PENGGUNAAN MEDIA -AUDIO VISUAL UNTUK MENINGKATKAN MOTIVASI SISWA BELAJAR MUSIK ANSAMBLE KELAS VIII-A SMP NEGERI 15 KOTA TASIKMALAYA - Fatimah, Fatimah (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
Learning media in the form of books, radio broadcasts, recorded events, films, computers, and television have the potential to grow and develop learning communities. Therefore, every teaching and learning activity to achieve educational goals, the use of media cannot be ignored. Teacher is a career position. Functional and professional, a member of the community who is competent (capable, able and authorized) and gains the trust of the community and/or government to carry out the duties, functions and roles and responsibilities of teachers, both in school-line educational institutions and out-of-school institutions. Teachers who have not mastered learning will be left behind by the flow of information and communication developments. A creative alternative for that is learning that is able to balance the work of the left and right hemispheres of the brain. The left brain plays an important role in the processing of logic, words, mathematics and sequences or what is known as the brain related to academic learning. While the right brain is related to rhythm, music, pictures, colors, space and imagination or what is known as the brain which is related to creative activity. The combination of the work of the two hemispheres in a lesson is what can reproduce the creativity of mastering learning concepts. The proper implementation of learning media for this is "Audio Visual". This media is the best technique in helping the brain's thinking process regularly because it uses graphical techniques derived from human thought which are useful for providing universal keys so as to unlock the potential of the brain. So that the summarized subject matter becomes visually and graphically patterned which can ultimately help record, strengthen, and recall the information that has been learned. This research was conducted in class VIII-A, with the following learning outcomes data: 1) the average interest and motivation in the two cycles was 75.5%, and in the high category; 2) the average activity / process skills in the two cycles are very high; "Audio Visual Media" is proven to be able to increase motivation to learn Arts and Culture and student activities in class VIII-A SMPN 15 Tasikmalaya, on the material "Learning Musical Ensembles